2014
DOI: 10.1007/s10157-014-1050-6
|View full text |Cite
|
Sign up to set email alerts
|

High renal resistive index in hypertensive patients is also associated with serum homocysteine level

Abstract: High renal resistive index in hypertensive patients is associated with homocysteine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…A positive correlation between RRI and insulin resistance has been shown previously [5,6]. Insulin resistance has been also shown in subjects with BTM [7].…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…A positive correlation between RRI and insulin resistance has been shown previously [5,6]. Insulin resistance has been also shown in subjects with BTM [7].…”
Section: Introductionmentioning
confidence: 70%
“…HOMA-IR, homeostasis model assessment of insulin resistance; BTM, beta thalassemia minor; HDL, high-density lipoprotein; LDL, low-density lipoprotein. tients with hypertension [5]. Kawai et al [10] reported high values of RRI in a group of 143 hypertensive patients; similarly, Trovato et al [11] reported high RRI in 119 hypertensive individuals compared to 150 subjects with a normal blood pressure.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations